(untitled) (Anwer Khan Modern Medical College Journal, 2014)
Bangladesh is a country having high density of population in the world. Its fertility rate ranges from 4.1 to 5.49 and life expectancy is 66years while the total fertility rate of Asia is 2.2 and life expectancy 70 years. This descriptive type of cross sectional survey was carried out among 240 married women of reproductive age from July to December, 2012 in some villages of Keranigonj, Upazila, Dhaka. 73(31%) were practicing some methods of contraception, while 167 (69%) were not using it. OCP (Oral Contraceptive Pill) was the commonest method of contraception followed by Condoms 12(5%), Injectable 12(5%), Implant 12(5%) & Tubectomy 6(3%). None was found using IUCD and Traditional method ( withdrawal, rhythm method ) and emergency contraceptive method. The use of contraceptive was more common in grand multipara (p<0.01), >35 years old ladies (p<0.05). Non users of contraceptives in this study were 167 (69%) and the major reason for the non use was intention to have more children 53(31.46%) followed by pressure from the husband 21(12.35%), prohibition by the religion 18 (10.9%) and desire for son 17 (10.11%). Among the 73 contraceptive users 38 (52%) experienced side effects with the use of contraceptives. The commonest side effects were menstrual irregularities 17(23.8%) followed by change in body weight 8(11.19%). Frequency of contraceptive use was found comparatively low among rural married women despite high level of awareness. Desire for larger family, religious concerns and fear of side effects were the main factors responsible for non users. Religious scholars must play their role in clarifying many aspects regarding contraceptives. DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18767 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 14-18